Effect of Foot Reflexology on Blood Pressure in Patients with Stroke - Ali Mohammadpour; Atefeh Dehnoalian; Javad Mojtabavi (Tehran University of Medical Sciences, 2013)
Background & Aim: Vascular events and strokes are third leading causes of death worldwide. There are also major causes of human morbidity. Various pharmacological and non-pharmacological treatments are proposed to patients with stroke. The purpose of this study was to determine effect of foot reflexology, as a non-pharmacological procedure, on systolic and diastolic blood pressures in patients with stroke.   Methods & Materials: In this clinical trial, 68 patients with stroke were selected and divided randomly into two experiment (n=34) and control (n=34) groups. Each patient in the experiment group received foot reflexology for 30 minutes. Data were recorded in the demographic and blood pressure record form. Data were analyzed using t-tests and ANOVAs in the SPSS-20.   Results: There were no significant differences between the mean systolic and diastolic blood pressures of patients in experiment and control groups at baseline. The blood pressure was significantly reduced among the experiment group after receiving the foot reflexology (P<0.05). The mean systolic blood pressure was significantly reduced in the experiment group after 10 and 30 minutes of massage; and the diastolic blood pressure was reduced significantly in all measured times (P<0.05).   Conclusion: Results showed positive effects of foot reflexology on reducing blood pressure in patients with stroke. Foot reflexology should be recommended as a supplement treatment in patients with stroke.